Effects of air annealing on Fe-Si-B-M-Cu (M=Nb, Mo) alloys - Silveyra, Josefina María (2014)
Previous works have shown that Nb protects Finemet (Fe73.5Si13.5B9Nb3Cu1) against oxidation. Still, the material must be annealed in a controlled atmosphere to induce nanocrystallization, otherwise, the oxide layer that is formed, deteriorates the soft magnetic properties of the material. Since Nb may be replaced by Mo in Finemet without a significant change in its structure and performance, we studied the effect of the exchange on the oxidation resistance of the alloy. We found that replacing Nb by Mo enhanced oxidation resistance. While Nb-alloy’s permeability was 41.3% smaller when nanocrystallized in air than in vacuum, Mo-alloy’s permeability only decreased by 8.5%. Air annealing would simplify the manufacturing process of Finemet products.